“Por los que quieren un gobierno de avanzada popular”: Nuevas prácticas políticas en la campaña presidencial de la Democracia Cristiana, Chile, 1962–1964. - Labarca, José Tomás (Latin American Research Review, 2017)
This article examines the Chilean presidential election of 1964. The election witnessed the clash of two reformist candidates: Eduardo Frei Montalva, of the Christian Democracy, and Salvador Allende, the candidate of the Popular Action Front, a broad coalition of left-wing parties. Existing interpretations of Frei’s victory stress two key factors: a terror campaign and support of the political right. This article complements existing explanations by documenting the participatory development of Frei’s political program and by exploring the electoral strategy as a whole. Given that half the electorate had recently been enfranchised for the election, this article takes into account the new political practices promoted by the Christian Democracy. The effect of these new practices on political and social mobilization was to be felt beyond this particular election.